Case Study on Tacit Knowledge Management Systems within X Company - Wan, Jiangping; Zeng, Ming; Zhu, Yahui (Scientific Research, 2013)
Case study on tacit knowledge management system within X company includes the design of tacit knowledge management system (the recognition and acquisition of tacit knowledge), mechanisms (the factor analysis for the transition and sharing of tacit knowledge) and implementation (the sharing enterprise culture build, the effective incentive mechanism construct and the organization structure design). The evaluation system is established based on critical success factors (the recognition capability, the sharing standard, the sharing mechanism of tacit knowledge). The purpose of study is to improve tacit knowledge management system within enterprise.
Keywords: Explicit Knowledge; Tacit Knowledge; Knowledge Conversion; Tacit Knowledge Management Systems; Case Study